PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT BERBANTUAN MEDIA PUZZLE TERHADAP HASIL BELAJAR PADA MATA PELAJARAN MATEMATIKA KELAS IV UPT SPF SD NEGERI 101740 TANJUNG SELAMAT - Florensia Manurung; Regina Sipayung; Irmina Pinem; Patri Janson Silaban; Heka Maya Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low learning outcomes of fourth-grade students in mathematics, particularly in the topic of fractions, at UPT SPF SD Negeri 101740 Tanjung Selamat. Preliminary observations revealed that many students considered mathematics to be difficult and monotonous, which led to low motivation, boredom, and limited participation during learning activities. The learning process was still dominated by teacher-centered methods with minimal use of engaging instructional media. To address this problem, an innovative learning strategy was implemented through the cooperative learning model Teams Games Tournament (TGT) assisted by puzzle media. This research employed a quantitative experimental method using a one group pretest-posttest design: The population of the study consisted of all 32 fourth-grade students, who were selected through total sampling. Research instruments included a 40-item multiple-choice test and a student response questionnaire. Data were analyzed using normality testing, correlation analysis, and hypothesis testing with a t-test. The results indicated a significant improvement in students' learning outcomes after applying the TGT model. with puzzle media. The average pretest score prior to treatment was 56.12, whereas the average posttest score increased to 81.5. Correlation analysis showed a strong relationship between the use of TGT with puzzle media and student learning outcomes, with r_hitung = 0.650, which is greater than r_table = 0.349. Furthermore, the hypothesis test yielded t_count = 4.683, which exceeded t_table = 1.694, leading to the rejection of Ho and acceptance of Ha. In conclusion, the application of the Teams Games Tournament learning model assisted by puzzle media had a positive and significant effect on the mathematics learning outcomes of fourth-grade students at UPT SPF SD Negeri 101740 Tanjung Selamat.